ULTRASTRUCTURE OF THE ILEUM EPITHELIUM OF MELIPONA QUADRIFASCIATA ANTHIDIOIDES (HYMENOPTERA, APIDAE, MELIPONINAE) - Dacruzlandim, C. (Wiley-Blackwell, 1994)
Study of the epithelial morphology of a stingless bee ileum from the pyloric valve to the last portion of high absorptive cells shows that although the bee ileum is an anatomically undifferentiated tube, four types of epithelial cells along the tube (in addition to the valve cells) indicate physiological differentiation. The anterior end seems to be less active in reabsorption, while the posterior region contains cells with typical morphology of an ion pump and permits conclusions about the mechanisms of absorption in the posterior end of the intestine. (C) 1994 Wiley-Liss, Inc.